Family Resilience and Caregiver Burden with the Relapse of Schizophrenia in Padang - Bunga Permata Wenny; Rika Sarfika; Hema Malini; Dewi Eka Putri (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
To achieve good quality care as caregivers, families must have mechanisms to help them deal with difficult situations and minimize the risk of recurrence. Families often experience high emotional stress from seeing patients struggling with schizophrenic symptoms. Family resilience, often interpreted as the ability to overcome, adapt, and recover from challenges in caring for schizophrenic patients, involves various aspects, including emotional and social support, effective communication, understanding of schizophrenia, and the family's ability to manage challenging situations. .. This quantitative research is a cross-sectional design within three months at the Asylum Hospital. Prof. HB. Saanin Padang, with a total of 152 people, was analyzed using the Spearman rho test. The results showed that family resilience and caregiver burden had a reasonably strong relationship with the recurrence of schizophrenic patients in Padang City. Family resilience, which tends to be high, is influenced by the majority of the female sex group with child status and is not distracted by work because most decide not to work permanently. The condition of resilience is inversely proportional to the burden of caregivers, which are generally in the low category.